Marketing Strategies for Chinese Companies in Mainland China Cosmetic Industry - Zhao, Ruijia (2013)
The Chinese cosmetic industry is presenting an increasing trend recently. However, the local Chinese cosmetic brands are facing tough competition with the foreign brands. Majority of the market share has been dominated by the foreign brands. Faced with this situation, it is extremely necessary for Chinese companies to study the reason behind this phenomenon.